2018
DOI: 10.1002/mrd.22972
|View full text |Cite
|
Sign up to set email alerts
|

Timing of sperm capacitation varies reproducibly among men

Abstract: Sperm must mature functionally in the process of capacitation to become able to fertilize. Capacitation depends on membrane lipid changes, and can be quantitatively assessed by redistribution of the ganglioside GM1, the basis of the Cap‐Score™ sperm function test. Here, differences in Cap‐Score were compared among and within men at two time points. Ejaculates were liquefied, washed, and incubated for 3 hr under capacitating (Cap) conditions, then fixed and analyzed immediately (Day0); after being incubated 3 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Assays proposed over the years to fill these needs have not demonstrated efficacy at prospectively predicting the clinical outcome of generating a pregnancy (Barratt et al, 2018), and are often found to correlate with the traditional semen analysis parameters (Aitken, 2002;Giwercman et al, 2003;Hazary, Chaudhuri, & Wishart, 2001;Zini et al, 2009). Prospective data presented here strongly demonstrate that the Cap-Score, a measure quantifying the percentage of sperm that can capacitate and undergo acrosome exocytosis Moody et al, 2017;Ostermeier et al, 2018), successfully predicted low or high success at achieving pregnancy in three or fewer attempts at IUI. Yet from a clinical perspective, we know that male fertility does not simply switch between a binary "infertile" to "fertile"…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Assays proposed over the years to fill these needs have not demonstrated efficacy at prospectively predicting the clinical outcome of generating a pregnancy (Barratt et al, 2018), and are often found to correlate with the traditional semen analysis parameters (Aitken, 2002;Giwercman et al, 2003;Hazary, Chaudhuri, & Wishart, 2001;Zini et al, 2009). Prospective data presented here strongly demonstrate that the Cap-Score, a measure quantifying the percentage of sperm that can capacitate and undergo acrosome exocytosis Moody et al, 2017;Ostermeier et al, 2018), successfully predicted low or high success at achieving pregnancy in three or fewer attempts at IUI. Yet from a clinical perspective, we know that male fertility does not simply switch between a binary "infertile" to "fertile"…”
Section: Discussionmentioning
confidence: 80%
“…Cap‐Scores were highly reproducible among ejaculates within a man and had no relationship with traditional semen analysis parameters (Cardona et al, ). In addition, we showed at the level of single sperm, that those cells having the “capacitated” patterns were indeed those cells that could undergo acrosome exocytosis in response to ionophore (A23187; Moody et al, ) and progesterone (Ostermeier et al, ). Using repeated Cap‐Score values over time, we also found that the timing of capacitation differed among men but was consistent within a man (Ostermeier et al, ).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…This wide time range is associated with the vast heterogeneity of semen samples, resulting in spermatozoa subpopulations with different degrees of functionality and membrane cholesterol content (Buffone, Doncel, Marin Briggiler, Vazquez-Levin, & Calamera, 2004;Buffone, Verstraeten, Calamera, & Doncel, 2009). Likewise, a previous study reported that spermatozoa need to capacitate for at least 4 hr for properly recognize the oocyte's zona pellucida (Baibakov, Boggs, Yauger, Baibakov, & Dean, 2012) and another report demonstrated that the timing of capacitation in human spermatozoa differs among men but is reproducible within each individual (Ostermeier et al, 2018).…”
mentioning
confidence: 99%